2016
DOI: 10.5935/abc.20160024
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between GRACE Score and Epicardial Fat Thickness in non-STEMI Patients

Abstract: BackgroundGRACE risk score (GS) is a scoring system which has a prognostic significance in patients with non-ST segment elevation myocardial infarction (non-STEMI).ObjectiveThe present study aimed to determine whether end-systolic or end-diastolic epicardial fat thickness (EFT) is more closely associated with high-risk non-STEMI patients according to the GS.MethodsWe evaluated 207 patients who had non-STEMI beginning from October 2012 to February 2013, and 162 of them were included in the study (115 males, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…Additionally, positive correlation existed between EFT and BMI, HbA1C, and Tr-I measurements. Our results are in accordance with Gul et al (37) who investigated whether endsystolic and end-diastolic EFT was more closely associated with NSTEMI patients according to the Global Registry of Acute Coronary Events (GRACE) risk score (GS). They found that both endsystolic and end-diastolic EFT values were increased in high GS patients as compared to those of low-moderate GS patients.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, positive correlation existed between EFT and BMI, HbA1C, and Tr-I measurements. Our results are in accordance with Gul et al (37) who investigated whether endsystolic and end-diastolic EFT was more closely associated with NSTEMI patients according to the Global Registry of Acute Coronary Events (GRACE) risk score (GS). They found that both endsystolic and end-diastolic EFT values were increased in high GS patients as compared to those of low-moderate GS patients.…”
Section: Discussionsupporting
confidence: 82%
“…38,[43][44][45] One study 43 found a significant association between EAT and GRACE scores (p <0.001), though this was not corroborated by other studies. 38 The angiographic SYNTAX score for coronary lesion severity and the clinical TIMI risk score for adverse coronary events were also found to be significantly linked with EAT.…”
Section: Eat and Acs Risk Scoresmentioning
confidence: 62%
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read the article "The Relationship between GRACE Score and Epicardial Fat Thickness(EFT) in non-STEMI Patients" by Gul et al 1 The authors concluded that end-systolic and end-diastolic EFTs were found to be increased in the higher GRACE group.…”
mentioning
confidence: 99%